The efficacy of intranasal leptin for opioid-induced respiratory depression depends on sex and obesity state - Singer, Michele L.; Shin, Mi-Kyung; Kim, Lenise J.; Freire, Carla; Aung, O; Pho, Huy; East, Joshua A.; Sgambati, Frank P.; Latremoliere, Alban; Pham, Luu V.; Polotsky, Vsevolod Y. (Frontiers in Physiology, 2023)
Introduction: Opioid-induced respiratory depression (OIRD) is the primary cause of death associated with opioids and individuals with obesity are particularly susceptible due to comorbid obstructive sleep apnea (OSA). Repeated exposure to opioids, as in the case of pain management, results in diminished therapeutic effect and/or the need for higher doses to maintain the same effect. With limited means to address the negative impact of repeated exposure it is critical to develop drugs that prevent deaths induced by opioids without reducing beneficial analgesia. Methods: We hypothesized that OIRD as a result of chronic opioid use can be attenuated by administration of IN leptin while also maintaining analgesia in both lean mice and mice with diet-induced obesity (DIO) of both sexes. To test this hypothesis, an opioid tolerance protocol was developed and a model of OIRD in mice chronically receiving morphine and tolerant to morphine analgesia was established. Subsequently, breathing was recorded by barometric plethysmography in four experimental groups: obese male, obese female, lean male, and lean female following acute administration of IN leptin. Respiratory data were complemented with measures of arterial blood gas. Operant behavioral assays were used to determine the impact of IN leptin on the analgesic efficacy of morphine. Results: Acute administration of IN leptin significantly attenuated OIRD in DIO male mice decreasing the apnea index by 58.9% and apnea time by 60.1%. In lean mice leptin was ineffective. Blood gas measures confirmed the effectiveness of IN leptin for preventing respiratory acidosis in DIO male mice. However, IN leptin was not effective in lean mice of both sexes and appeared to exacerbate acid-base disturbances in DIO female mice. Additionally, morphine caused a complete loss of temperature aversion which was not reduced by intranasal leptin indicating IN leptin does not decrease morphine analgesia. Discussion: IN leptin effectively treated OIRD in morphine-tolerant DIO male mice without impacting analgesia. In contrast, IN leptin had no effect in lean mice of either sex or DIO female mice. The arterial blood gas data were consistent with ventilatory findings showing that IN leptin reversed morphine-induced respiratory acidosis only in DIO male mice but not in other mouse groups. Finally, a hypercapnic sensitivity study revealed that IN leptin rescued minute ventilation under hypercapnic conditions only in DIO male mice, which suggests that differential responses to IN leptin are attributable to different leptin sensitivities depending on sex and the obesity status.